2011
DOI: 10.1111/j.1464-410x.2011.10733.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of local treatment with iloprost, a prostacyclin analogue, in patients with Peyronie's disease: a phase I study

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Peyronie's disease (PD) is an acquired curvature of the penis attributable to progressive fibromatosis of the tunica albuginea (TA). It is frequently associated with Dupuytren's contracture and those of Ledderhose. More recently it was found that patients suffering from PD also often suffer from diabetes mellitus and gout. Cigarette smoking and the intake of large amounts of alcohol are considered r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In contrast to the above findings, intralesional injection with verapamil, IFN α‐2b or CCH has shown efficacy in improving penile curvature, reducing plaque size and density, and reducing penile pain . In addition, an initial, non‐controlled study has suggested safety and tolerability of intralesional iloprost in patients with PD; however, further study with placebo comparison is required . Results from a single‐blinded, placebo‐controlled study of 14 men receiving intralesional verapamil over 6 months showed significantly decreased plaque volume compared with placebo (1.42 cm 3 to 0.63 cm 3 in verapamil‐treated men vs. 1.37 cm 3 to 1.39 cm 3 in controls), with a trend towards improvement in penile curvature (mean improvement from pretreatment 37.7° to posttreatment 29.6° in verapamil‐treated patients vs. 33.6° to 31.4° in controls) .…”
Section: Treatment Considerationsmentioning
confidence: 97%
“…In contrast to the above findings, intralesional injection with verapamil, IFN α‐2b or CCH has shown efficacy in improving penile curvature, reducing plaque size and density, and reducing penile pain . In addition, an initial, non‐controlled study has suggested safety and tolerability of intralesional iloprost in patients with PD; however, further study with placebo comparison is required . Results from a single‐blinded, placebo‐controlled study of 14 men receiving intralesional verapamil over 6 months showed significantly decreased plaque volume compared with placebo (1.42 cm 3 to 0.63 cm 3 in verapamil‐treated men vs. 1.37 cm 3 to 1.39 cm 3 in controls), with a trend towards improvement in penile curvature (mean improvement from pretreatment 37.7° to posttreatment 29.6° in verapamil‐treated patients vs. 33.6° to 31.4° in controls) .…”
Section: Treatment Considerationsmentioning
confidence: 97%
“…Additional investigational agents for PD treatment include liposomal recombinant human superoxide dismutase (lrhSOD, also known as orgotein),[ 66 67 83 84 85 ] iloprost,[ 87 ] and Peironimev-Plus ® . [ 60 ] The use of intralesional lrhSOD has only been described in observational studies,[ 83 84 85 ] while topical lrhSOD has been evaluated in one observational study[ 66 ] and one crossover RCT with promising results.…”
Section: Future Directionsmentioning
confidence: 99%
“…Iloprost is a prostacyclin analog recently tested as a potential intralesional PD therapy, chosen because of its anti-transforming growth factor (TGF)-β activity in fibroblasts. [ 87 ] Additional potentially beneficial effects of prostacyclin include vasodilation, activation of fibrinolysis, and inhibition of platelet function, leukocyte migration, and cell adhesion molecule expression. Improvement in penile curvature was observed in 29% of 38 treated patients, but these data are difficult to interpret given the lack of a placebo comparison group.…”
Section: Future Directionsmentioning
confidence: 99%
“…Surgery is indicated when disease is stabilized [12,13] and in patients with severe penile curvature and/or erectile dysfunction [14]. Nonsurgical treatments include: potaba, Vitamin E, colchicine, tamoxifen, propolis, verapamil, interferons, collagenase, cortisone, pentoxifylline, iloprost, iontophoresi, Extracorporeal Shock Wave Therapy (ESWT) and Capacitive Resistive Energy Transfer (Tcare or TECAR therapy) [15][16][17][18][19][20][21]. Since we have already experienced the effectiveness of conservative treatment in the early phase of PD [17,[22][23][24], we implemented a controlled study on patients with PD treated in association with several drugs: Pentoxifylline plus several antioxidants (Vitamin E, blueberries and propolis) and topical Diclofenac.…”
Section: Introductionmentioning
confidence: 99%